Pencegahan Penipuan Social Engineering pada Massa 4.0 - Ryan Triwahono, Dimas; Fauzi, Achmad; Adzansyah, Adzansyah; Yulivio, Belva; Yusuf Fito, Muhammad; Ghifari Putra Yuntama, Reynaldo; Waliyudin Azhar, Satrio (Jurnal Ilmu Multidisiplin, 2023)
This paper intends to explore three social design related online protection issues facing organizations and develop techniques to stop human trickery in friendly design attacks. Twenty experts in Branch Security Information Structures took part in a three-round Delphi study to unify and refine the feeling of high quality. The three rounds move the individual towards a setting for guidelines against attacks with friendly plans in affiliates. Three basic problems: compromised data; inadequate training; and the lack of sophisticated training drives the three target areas to apply best practices against social plan attacks. The invention provides countermeasures by coordinating high-level training, techniques, cycles, and preparation into safety exercises. This study adds to the field of organizational security with an emphasis on trust and human creativity to examine counter-accommodation counter-accommodation attack plans. This paper adds to the set of underrepresented underrepresented social program monitoring implementation of social programs.